Molecular characterization of Amitermes rhizophagus Belyaeva, 1974 (Blattodea: Isoptera), newly recorded from Uzbekistan - Mirzaeva, Gulnara S.; Kholmatov, Bakhtiyor R.; Rustamov, Kakhramon D.; Ganieva, Zumrad A.; Akhmedov, Vakhidjon N.; Lebedeva, Natalia I.; Khashimova, Mukhabbat Kh.; Sobirov, Sobir K.; Amirov, Oybek A.; Allaberdiyeva, Kumri X. (Acta Biologica Sibirica, 2025)
This study presents the first molecular confirmation of Amitermes rhizophagus Belyaeva, 1974 (Blattodea: Termitidae) from Uzbekistan. Specimens collected in the Kashkadarya Region were identified through combined morphological and molecular analyses. Ribosomal DNA (ITS) and mitochondrial DNA (COI) fragments were amplified, sequenced, and compared with reference sequences from GenBank. Phylogenetic analyses using the Maximum Likelihood method placed A. rhizophagus within a well-supported Amitermes clade (bootstrap = 98-100%), closely related to A. deplanatus, A. conformis, and A. foreli. Genetic distances were low within Amitermes (0.017-0.034) but high between genera (0.13-0.19), confirming clear evolutionary separation from Drepanotermes and Microcerotermes. These findings validate the taxonomic identity of A. rhizophagus and provide the first molecular evidence for its occurrence in Uzbekistan, enriching knowledge of Central Asian termite diversity and phylogeny.